The Influence of Brand Image and Product Quality on Purchase Decisions for Acer Laptop Products in the Surabaya Region - Hakim, Dwinanda Firman; Wardhani, Nuruni Ika Kusmuma (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
In the digital era, laptops are a technology needed by everyone, both in the world of education and the world of work. In the rapidly developing technology industry, there is a lot of competition among laptop manufacturers. With so much competition for laptop products on the market, the market share of Acer's laptop products will decline in 2020 and 2021. Therefore, researchers formulate the problem of whether brand image and product quality affect purchasing decisions. This study aims to analyze the effect of brand image and product quality on purchasing decisions for Acer laptop products in the Surabaya area. The sample in this study is people who live in the Surabaya area and users of Acer laptop products, as many as 72 respondents. The sampling method used is Partial Least Square (PLS). The mechanism used is Non Probability Sampling using the sample purposive sampling method. This research shows that Brand Image and Product Quality have a significant effect on purchasing decisions for Acer laptop products in the Surabaya area.